Idosos em processo demencial e a fonoaudiologia: um estudo de caso - Mello, Jayne Guterres de (2014)
Purpose: analyzing verbal expression and interpretation/comprehension and underlying mechanisms (hearing, body balance, voice and orofacial motricity) of two elder women with clinical case of dementia one living in family environment and other in an elderly Long Permanence Institution. Materials and methods: field investigation, transversal, qualitative, presented in case study modality. Took part two elderly one non-institutionalized with Alzheimer Dementia, the other institutionalized with Vascular Dementia, valued according to a speech evaluation script that beholds in integrated way aspects of language, hearing, body balance, voice and orofacial motricity. Oral language was evaluated through interview, narrative of a relevant fact in life and a present one, comments, evocation/interpretation of a proverb, interpretation of syllogism, resolving a daily problem and yet the expression space-time location conditions. The hearing was evaluated by pure tone audiometry, speech audiometry, behavioral tests of hearing processing and Long-Lantency Auditory Evoked Potential (LLAEP); body balance through static balance tests, dynamic and movements coordination and Sensory Organization Test; voice through perceptive-hearing analysis; and orofacial motricity through observation of structures and functions of the stomatognathic system, highlighting swallowing dynamics. Results: obtained the elaboration of a protocol version of speech evaluation that seizes the operation of language, hearing, body balance, voice and orofacial motricity. In the elderly' evaluation were found linguistic-cognitive manifestation more compromised in the institutionalized elderly. The results of the organic-physiological aspects evaluation, in both elderly, matches the natural aging process. Conclusions: the script favors accurate diagnoses; the elderly' organic-physiological conditions were compatible with natural aging process, while linguistic-cognitive conditions present more compromised. This report shows the convenience of speech therapist acting at aging, especially with dementia, as much in family as in institutional context.